ANALISIS PENGARUH FRAUD DIAMOND DAN RELIGIUSITAS TERHADAP KECURANGAN AKADEMIK (ACADEMIC FRAUD): STUDI PADA MAHASISWA AKUNTANSI UNIVERSITAS SYIAH KUALA DISAAT PEMBELAJARAN JARAK JAUH (PJJ) - Siregar, Nella Sari; Kamal, Maulana (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This paper seeks to examine a variety of hypotheses related to diamond fraud theory and religiosity on academic fraud. Using the purposive sampling method, this study involves 197 students of Accounting Study Program at Faculty of Economics and Business Syiah Kuala University during the implementation of Distance Learning. Data were collected using a questionnaire and distributed via google form. The results show that pressure and opportunity have positive significant effect on academic fraud, ability and religiosity have negative significant effect on academic fraud, and rationalization has no significant effect on academic fraud.